2014
DOI: 10.1515/jpem-2013-0317
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and body composition during the transition phase in patients treated with recombinant GH to final height

Abstract: We assessed body composition and muscle strength during the transition phase in 18 growth hormone (GH) deficient males treated with recombinant GH to final height and 18 controls. According to peak-stimulated GH and basal insulin-like growth factor-1 (IGF-1) during the transition phase, patients were subdivided into GH deficient (GHD-TP, n=9) and GH sufficient (GHS-TP, n=9) groups. Assessments included lean and fat body mass and bone mineral density (BMD), all measured by dual-energy X-ray absorptiometry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…From a recently published cross-sectional study investigating muscle strength and body composition of 18 males with CO-GHD (aged 18–30 years), of those, 9 (4-IGHD) were reconfirmed to have GHD after re-evaluating them at final height during transition. This study suggested that muscle strength as measured by an isokinetic dynamometer was lower in those with persistent GHD compared with sufficient and healthy controls ( P <0.05) (13). However, data so far do not support the use of rhGH therapy to increase muscle strength during transition and young adulthood (16, 21, 39).…”
Section: Consequences Of Rhgh Cessation and Replacement During Transimentioning
confidence: 90%
See 1 more Smart Citation
“…From a recently published cross-sectional study investigating muscle strength and body composition of 18 males with CO-GHD (aged 18–30 years), of those, 9 (4-IGHD) were reconfirmed to have GHD after re-evaluating them at final height during transition. This study suggested that muscle strength as measured by an isokinetic dynamometer was lower in those with persistent GHD compared with sufficient and healthy controls ( P <0.05) (13). However, data so far do not support the use of rhGH therapy to increase muscle strength during transition and young adulthood (16, 21, 39).…”
Section: Consequences Of Rhgh Cessation and Replacement During Transimentioning
confidence: 90%
“…Cross-sectional and observational studies of bone density in rhGH-treated children with CO-GHD at time of completing linear growth have shown inconsistent findings with either low areal bone mineral density (BMD) (g/cm 2 ), normal or slightly reduced total body (TB) BMD, bone mineral density (BMC) and lumber spinal (LS) volumetric mineral apparent density (BMAD) (g/cm 3 ) (9, 10, 11, 12, 13) (Table 1). Early rhGH treatment in childhood results in better indices of bone mass on completion of treatment at final height (9).…”
Section: Consequences Of Rhgh Cessation and Replacement During Transimentioning
confidence: 99%
“… 4 , 41 In terms of muscle strength, previous studies have reported a lower maximum isotonic strength in young adults with CO-GHD, as measured by hand grip force, 53 , 54 but the effects on muscle strength in adolescents with CO-GHD during transition still remain to be completely elucidated. 55 There are some suggestions that reduced muscle mass was the cause of diminished muscle strength in GHD, as opposed to a reduction in contractile function. 56 Furthermore, it has been proposed that CO-GHD may initially result in a reduction in muscle mass and force, which would ultimately have an impact on bone density and geometry.…”
Section: Introductionmentioning
confidence: 99%